極域温暖化問題の概観 - 山内, 恭; ヤマノウチ, タカシ; Yamanouchi, Takashi (2016)
P(論文) 今，北極・南極は温暖化しているのだろうか？ この質問に答えられるように，解説を試みた．近年の地球温暖化の中で，強い温暖化の現れている地域は北極域と南極半島域である．北極域の温暖化は全球平均の2倍以上の温暖化で，北極海の夏の海氷も著しく減少している．何がこの北極温暖化増幅をもたらしているのか，その原因を探った．一方，南極では，南極半島や西南極で温暖化が激しいのに対し，東南極では温暖化が顕著にはみえない．なぜ，温暖化が抑えられているのであろうか．オゾンホールが関係しているという説を述べる．さらに，北極温暖化の影響で，中緯度に寒冷化が起こる現象がみつけられ，様々な議論を呼んでいる．今後の研究が期待される． Are the Arctic and Antarctic really warming now? This review was performed in order to answer this question. In the recent, the strongest warming occurred in the Arctic and Antarctic Peninsula under the global warming. Warming in the Arctic is more than twice the global average, and sea ice has rapidly reduced in summer. A contribution of each processes have been investigated to determine which play the largest role in this Arctic warming amplification. On the other hand, despite strong warming in the Antarctic Peninsula and West Antarctica, no meaningful warming has been seen in East Antarctica. What is the reason for this suppressed warming in East Antarctica? There has been some speculation that the ozone hole has been working as a suppressor of warming. Another effect of the Arctic warming is its influence on extreme weather in the mid-latitudes. Much current research is focused on the effect of Arctic warming on mid-latitude weather, with the aim of increasing our understanding of interaction between these regions. departmental bulletin paper